ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNTUNGAN USAHA KERIPIK NENAS DI KABUPATEN KAMPAR - Riska Dian Oktari; Lestari Rahayu Waluyati; Any Suryantini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The purposes of the research to know the factors that affect the profits in the pineapple chips business. The research was conducted in Tambang Sub-district Kampar Regency Riau Province where the location selection for the research was conducted purposively i.e. selecting the location intentionally, while the method of collecting data was using census method. Research method was using multiple linear regression analysis with OLS (Ordinary Least Square) to determine the factors that affect the profit. The results showed that the factors that affected the profit of pineapple chips business were baking soda prices, shrinkage of vacuum frying machine, the frequency of production and yield, while raw material prices, the price of cooking oil and labor costs did not give a significant influence on profits.